AduCPI2 alleviates MSU-induced acute gouty arthritis in mice by inhibiting cathepsin S and the C5a-C5aR1 axis - Liu, Sijing; Situ, Yongli; Deng, Li; Liang, Meng; He, Haoyuan; Shao, Zheng; Peng, Lifei (Frontiers in Pharmacology, 2025)
BackgroundGout, a prevalent and severe form of arthritis precipitated by hyperuricemia, has been the subject of extensive research. However, the intricate underlying mechanisms governing gout-related inflammation are still only partially elucidated. Ancylostoma duodenale cysteine protease inhibitor 2 (AduCPI2, abbreviated as CPI2, GenBank No. JQ762417) is a protein isolated from A. duodenale by our research group in the early stage. CPI2 can effectively inhibit the activity of cathepsin S and reduce the level of C5a. In this study, we aimed to investigate the effect of CPI2 on acute gouty arthritis stimulated by monosodium urate (MSU) crystals.MethodsThe CPI2 fusion protein was induced for expression in Escherichia coli with isopropyl β - D - 1 - thiogalactopyranoside (IPTG). The recombinant CPI2 fusion protein was purified via Ni-NTA affinity chromatography and SP Bio-sep FF ion exchange chromatography. The fusion tag was cleaved by SUMO protease to yield the purified CPI2 protein. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was employed to analyze the protein expression and purification status. An enzyme activity inhibition assay was conducted to detect the inhibitory effect of CPI2 on cathepsin S. In an attempt to mimic human gouty arthritis, suspensions of monosodium urate (MSU) crystals were injected into the right foot pads of C57BL/6 wild-type (WT) mice and C5aR1−/− mice. After the injection of MSU crystals, the mice were intravenously administered CPI2 at doses of 0.5, 1, and 2 mg/kg body weight. The effects of CPI2 on mice with MSU-induced gouty arthritis were evaluated by measuring the degree of paw swelling, observing the histopathological changes in paw tissues using hematoxylin and eosin (HE) staining, detecting the levels of inflammatory cytokines, C5a, and cathepsin S by enzyme-linked immunosorbent assay (ELISA), determining the activities of glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) as well as the level of malondialdehyde (MDA) by chemiluminescence assay, and observing the expression level of C5aR1 protein in paw tissues by immunohistochemistry.ResultsAfter culturing in E. coli, induced expression, and isolation-purification, CPI2 with a purity of over 98% was finally obtained. CPI2 ameliorated the inflammation of MSU-induced gouty arthritis in a dose-dependent manner. It reduced joint swelling, decreased the infiltration of inflammatory cells, lowered the levels of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α), increased the level of the anti-inflammatory cytokine IL-10, enhanced the activities of SOD and GSH-Px, while reducing the content of MDA, decreasing the levels of C5a and cathepsin S, and down-regulating the expression level of C5aR1 protein. The knockout of the C5aR1 gene was beneficial for inhibiting the inflammation of MSU-induced gouty arthritis.ConclusionCPI2 alleviates MSU-induced acute gouty arthritis in mice through the inhibition of cathepsin S and the C5a - C5aR1 axis. CPI2 may represent a potential candidate for the treatment of gouty arthritis.